Legal Uncertainty, Criminal Liability, and Justice in Adolescent Cyberbullying Cases - Rajwa, Zalfa Aqilah; Anurakphong, Kiranut Thamwiset; Wattanakul, Nalinrada Pimsuda; Arifin, Ridwan; Rochman, Auliya (UIR Press, 2026)
The rapid expansion of digital technology has intensified the phenomenon of cyberbullying, with adolescents constituting a particularly vulnerable group. This study examines legal uncertainty in the construction of criminal liability for cyberbullying perpetrators and evaluates the effectiveness of its enforcement within the Indonesian criminal justice system. Employing a normative-empirical juridical method, the research analyzes statutory frameworks, including the Information and Electronic Transactions Law and the Indonesian Criminal Code, alongside selected court decisions with permanent legal force. The findings reveal that although existing legal instruments may be used to prosecute cyberbullying-related conduct, the absence of an explicit legal definition of cyberbullying generates interpretative ambiguity and inconsistency in the application of offense elements. Furthermore, structural constraints such as limited digital forensic capacity and procedural challenges in evidence collection weaken enforcement effectiveness. Socio-cultural factors, including stigma and low reporting rates among adolescent victims, further exacerbate under-enforcement. This study highlights that the current legal framework has not yet adequately addressed the specific characteristics of cyberbullying as a digitally mediated form of harm. It recommends regulatory harmonization through the explicit codification of cyberbullying as a distinct offense, alongside strengthening institutional capacity and promoting digital literacy as a complementary non-penal preventive strategy. The study contributes to ongoing debates on cybercrime regulation and child protection in digital environments.